Proprioceptive activities to postural balance of the elderly - systematic review - Adriano Drummond; Clarissa Cardoso dos Santos Couto Paz; Ruth Losada de Menezes (Editora Champagnat, 2018)
Abstract Introduction: Proprioceptive activities are commonly described for control of the postural balance of the elderly in order to avoid falls. But, there is no consensus on which ones can significantly improve balance or on intervention and assessment protocols. Objective: To investigate which proprioceptive activities are specific to static and dynamic postural balance of the elderly through a systematic review. Method: This is a systematic review based on PRISMA recommendation, by surveying PubMed, Medline, LILACS, Scielo and EBSCO databases. The period considered for the search was from 2006 to 2016, using the following descriptors - aged, proprioception, exercise therapy, and postural balance for articles in English, Portuguese or Spanish. Randomized and non-randomized clinical trials were included using the PEDro scale to analyze the methodological quality of the studies. Results: Eight articles were included with different protocols, without standardization of evaluation and intervention, but, which demonstrated improvement of functional abilities. Different kinds of walk, muscular strengthening exercises, stretching, postural oscillations and Yoga patterns for the improvement of functional abilities. Conclusion: The association of static and dynamic activities can contribute to the improvement of functional abilities, but it cannot be affirmed that they are specific for postural control, given the lack of standardization of exercise protocols and evaluation tools.